2017
DOI: 10.1016/j.wavemoti.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Upholding the diffraction limit in the focusing of light and sound

Abstract: The concept of the diffraction limit put forth by Ernst Abbe and others has been an important guiding principle limiting our ability to tightly focus classical waves, such as light and sound, in the far field. In the past decade, numerous reports have described focusing or imaging with light and sound 'below the diffraction limit'. We argue that the diffraction limit defined in a reasonable way, for example in terms of the upper bound on the wave numbers corresponding to the spatial Fourier components of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 66 publications
(107 reference statements)
0
23
0
2
Order By: Relevance
“…Thus, the transmission efficiency of an acoustic lens with a narrower FWHM is generally more decreased. The physical basis for this phenomenon can be more reliably supported from 4 . Consequently, the focusing performance and the transmission efficiency have a trade-off relationship to each other.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, the transmission efficiency of an acoustic lens with a narrower FWHM is generally more decreased. The physical basis for this phenomenon can be more reliably supported from 4 . Consequently, the focusing performance and the transmission efficiency have a trade-off relationship to each other.…”
Section: Resultsmentioning
confidence: 95%
“…Finally 4 clarified more reasonable criteria about overcoming the diffraction limit in the focusing application as the following two: (1) The smallest period of the spatial Fourier components in the image plane is less than λ/2, (2) More than approximately 50% of the incident acoustic power is focused in the main focusing area. Indeed, our study has focused on the first criterion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Как в оптике, так и в акустике критерий Рэлея [2] устанавливает предел поперечного разрешения в дальнем поле равного λ/2. Преодолеть этом предел возможно с помощью специальных линз из метаматериалов [3][4][5][6][7]. Экспериментально было показано, что можно достичь разрешение равное λ/2 [8][9][10].…”
Section: The Possibility Of Focusing the Acoustic Radiation Into A Reunclassified
“…Acoustic power of up to ∼ 1 kW is readily achievable with medical high-intensity focused ultrasound (HIFU) transducers that have a ∼ 50% electrical-to-acoustic conversion efficiency [36]. Moreover, it has been shown that the focal area of the transducer may be reduced by using acoustic metamaterials, which allows focusing ultrasound into deep-subwavelength, 1/40 of the incident wavelength spots [37]. Thus, the required acoustic power may be decreased to ∼ 20 mW.…”
mentioning
confidence: 99%